The amplified cancer gene LAPTM4B promotes tumor growth and tolerance to stress through the induction of autophagy - Li, Yang (Landes Bioscience, 2012)
Autophagy is a fundamental salvage pathway that encapsulates damaged cellular components and delivers them to the lysosome for degradation and recycling. This pathway usually conducts a protective cellular response to nutrient deprivation and various stresses. Tumor cells live with metabolic stress and use autophagy for their survival during tumor progression and metastasis. Genomic instability in tumor cells may result in amplification of crucial gene(s) for autophagy and upregulate the autophagic pathway. We demonstrate that a cancer-associated gene, LAPTM4B, plays an important role in lysosomal functions and is critical for autophagic maturation. Its amplification and overexpression promote autophagy, which renders tumor cells resistant to metabolic and genotoxic stress and results in more rapid tumor growth.